(499) Lecture Notes in Operations Research Related Topics to Linear Programming ملاحظات المحاضرات في بحوث العمليات: مواضيع ذات صلة بالبرمجة الخطية - محمد الكفراوي (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة تطبيقات متقدمة في "بحوث العمليات"، مع التركيز بشكل خاص على الامتدادات والنماذج المرتبطة بـ "البرمجة الخطية" ستعرض البحث بعمق "مشكلة النقل" (Transportation Problem) كحالة خاصة تتميز ببساطتها الحسابية وقابليتها للتطبيق في مجالات اقتصادية وصناعية متنوعة، موضحاً بالنماذج الرياضية والأمثلة العملية (مثل شركة النصر للتليفزيون) كيفية الوصول للتوزيع الأمثل للمنتجات من المصانع إلى الأسواق لتحقيق أقصى ربح أو أدنى تكلفة ممكنة، مع شرح لأساليب "التعيين" (Assignment Problem) لتخصيص الأفراد للوظائف المناسبة بناءً على كفاءتهم (، كما يخصص الملف جزءاً كبيراً لـ "البرمجة الصحيحة" (Integer Programming)، وهي النماذج التي تتطلب أن تكون الحلول في صورة أعداد صحيحة فقط، مبيناً أهميتها في الحالات التي لا تقبل التجزئة ، ويشرح البحث بالتفصيل خوارزميات معقدة للحل مثل "خوارزمية جوموري" (Gomory's Algorithm) التي تعتمد على توليد "قيود قاطعة" (Cutting Planes) لتقليص منطقة الحلول الممكنة وصولاً للحل الصحيح الأمثل، بالإضافة إلى أسلوب "الفرع والحد" (Branch and Bound)، مما يوفر للمخططين والباحثين أدوات رياضية قوية لإدارة الموارد واتخاذ قرارات دقيقة تدعم كفاءة العمليات التشغيلية في المؤسسات القومية . This paper explores advanced applications in operations research, with a particular focus on extensions and models related to linear programming. It will delve deeply into the transportation problem as a special case, characterized by its computational simplicity and applicability across diverse economic and industrial sectors. Using mathematical models and practical examples (such as Al-Nasr Television Company), it will demonstrate how to achieve optimal product distribution from factories to markets to maximize profit or minimize costs. The paper will also explain assignment problem techniques for assigning individuals to suitable jobs based on their competence. A significant portion of the paper is dedicated to integer programming, which requires solutions to be integers only. The importance of integer programming is highlighted in cases where indivisibility is not possible. The paper will explain in detail complex solving algorithms such as Gomory's Algorithm, which uses cutting planes to narrow down the range of possible solutions to arrive at the optimal correct solution. Finally, it will cover branch and limit methods. and Bound), providing planners and researchers with powerful mathematical tools for resource management and accurate decision-making that support the efficiency of operational processes in national institutions.